2022
DOI: 10.3389/fcell.2022.926776
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Cell-specific Roles of NOX2 and MyD88 in Epileptogenesis

Abstract: It is well established that temporal lobe epilepsy (TLE) is often related to oxidative stress and neuroinflammation. Both processes subserve alterations observed in epileptogenesis and ultimately involve distinct classes of cells, including astrocytes, microglia, and specific neural subtypes. For this reason, molecules associated with oxidative stress response and neuroinflammation have been proposed as potential targets for therapeutic strategies. However, these molecules can participate in distinct intracell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 77 publications
0
4
0
Order By: Relevance
“…Among the NOX isoforms, NOX2 has been particularly related to neuronal damage and death, as well as to the resolution of the subsequent inflammatory response after brain injury including SE [ 72 ]. It is argued that besides being the major contributor to SE-induced ROS production in acquired epilepsies, NOX2, expressed mainly in microglia, is thought to be the major contributor to the neuroinflammation response [ 73 ]. In agreement with these data, we demonstrated that NOX2 was also expressed in the cortex, as well as in CA1 and CA3 of the hippocampus 1 week after SE ( Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Among the NOX isoforms, NOX2 has been particularly related to neuronal damage and death, as well as to the resolution of the subsequent inflammatory response after brain injury including SE [ 72 ]. It is argued that besides being the major contributor to SE-induced ROS production in acquired epilepsies, NOX2, expressed mainly in microglia, is thought to be the major contributor to the neuroinflammation response [ 73 ]. In agreement with these data, we demonstrated that NOX2 was also expressed in the cortex, as well as in CA1 and CA3 of the hippocampus 1 week after SE ( Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Whether HCAR1 influences epileptogenesis leading to chronic recurrent epileptic events has still to be determined. Epileptogenesis is a complex process driven by oxidative stress and neuroinflammation 68 and involving cellular and network reorganization, that includes ryanodine receptors and various synaptic proteins. 69 The understanding of factors favoring epileptogenesis will likely benefit from omics approaches, such as the analysis of plasma proteins used as biomarkers in individuals experiencing recent and recurrent seizures.…”
Section: Discussionmentioning
confidence: 99%
“…In the development of TLE, the involvement of OS and neuroinflammation have been well established as important factors, in part because the large amount of energy required by the brain is considered to be a possible mechanism involved in epileptogenesis [ 12 , 21 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 ]. In recent studies, it was observed that the specific inhibition of NADPH oxidase (NOX), the main producer of OS through O 2 •− synthesis, modified chronic epilepsy in a TLE rat model, preventing ROS generation, mitochondrial depolarization, and neuronal death.…”
Section: Discussionmentioning
confidence: 99%